The spirit of 1896 a mirror of the Philippine past, a window on the nation's future - Co, Jason; National Centennial Commission (Philippines).; University of the Philippines Press ([Manila] Philippine Centennial Commission University of the Philippines Press, 2000)
'The journey of a thousand miles starts with the first step. For the Filipino nation, that first step was the Revolution of 1896 and the founding of Asia's first free Republic. Even today's Filipinos are born with the ideals and the spirit of a people who had lost—then regained—their faith; a people who have struggled, suffered defeat, and survived it. And now it is time to remember the incredible sacrifice and courage that went into molding the congeries of Philippine tribes into one nation.'--Publisher.
Introduction: Freedom Gained...Fervor Lost? -- Sharing a Common Past: On the Need to Look Back -- Our Passion for Freedom: Its Imprint in Our History -- The Story of Our Revolutions, Through a Glass Clearly -- The Ideas and the Spirit of 1896: Their Relevance to Our Time -- The Soul of a Nation, Through a Bus Window -- The Last One Hundred Years: The Spirit of 1896 Lives on -- Revolution and Independence: 1896 at the Gem in the Philippine Centennial -- The Challenge for Us Today: A Crucial Test for the Spirit of 1896 -- Looking Ahead: Visions of the Nation a Century Hence -- A Summons to Greatness: The Call of the Revolution -- Renewing Our Pledge: Our Gift to the Future.
Cover subtitle: A mirror of the Philippine past, a window on its future.
Jointly published with the University of the Philippines Press.
Includes bibliographical references.
Centennial literary prize, 1898-1998, First prize/English essay.
Keywords: Philippines -- History -- Revolution, 1896-1898.